The First Ground‐Level Enhancement of Solar Cycle 25 as Seen by the High‐Energy Particle Detector (HEPD‐01) on Board the CSES‐01 Satellite. Issue 1 (25th January 2023) - Martucci, Matteo; Laurenza, Monica; Benella, Simone; Berrilli, Francesco; Del Moro, Dario; Giovannelli, Luca; Parmentier, Alexandra; Piersanti, Mirko; Albrecht, Gabor; Bartocci, Simona; Battiston, Roberto; Burger, William J.; et al.
Abstract: In this work we present the High‐Energy Particle Detector (HEPD‐01) observations of proton fluxes from space during the 28 October 2021 solar energetic particle event, which produced a ground‐level enhancement on Earth. The event was associated with the major, long‐duration X1‐class flare and the concomitant coronal mass ejection (CME) that erupted from the Active Region 12887. This is the first direct measurement from space of solar particles emitted during the current solar cycle, recorded by a single instrument in the energy range from ∼50 MeV/n up to ∼250 MeV/n. We have performed a Weibull‐modeled spectral analysis of the energy spectrum in the wide energy range 300 keV–250 MeV, obtained from combination of HEPD‐01 proton measurements with the ones from ACE/ULEIS, SOHO/EPHIN, and SOHO/ERNE. The good agreement between data and model, also corroborated by a comparison with other spectral shapes commonly used in these studies, suggests that particles could have possibly been accelerated out from the ambient corona through the contribution of stochastic acceleration at the CME‐driven shock, even if the presence of seed populations influencing spectral shape could not be excluded. Finally, a Solar Proton Release time of 16:01 UTC ± 13 min and a magnetic path‐length of L = 1.32 ± 0.24 AU have been obtained, in agreement with previous results for this event. We remark that new and precise data on protons in the tens/hundreds MeV energy range—like the one provided by HEPD‐01—could shed more light on particle acceleration as well as provide a reliable parametrization of solar energetic particle spectra for Space Weather purposes. Plain Language Summary: In this work we present the observation from space of protons emitted by the Sun during the 28 October 2021 solar event. This event was particularly strong and it was even registered at Earth by instruments called Neutron Monitors. Such highly energetic phenomena are rather rare and they can give a lot of information on particle acceleration and propagation from Sun to Earth. By using data from various spacecrafts, like High‐Energy Particle Detector, we were able to address some characteristics of this event, like its duration, the most probable mechanism that accelerate particles, the path traveled by such particles, as well as to constrain the time in which they are accelerated. Key Points: High‐Energy Particle Detector (HEPD‐01) measurements of solar protons (50–250 MeV) emitted during the first ground‐level enhancement of solar cycle 25 Spectral analysis conducted on a energy‐extended, time‐integrated proton spectrum using also ACE, ERNE, and EPHIN data Time‐of‐arrival analysis in good agreement with the literature and highlights the central role of HEPD‐01 at energies around hundreds of MeV